Conflict Structuration in Audit Findings Negotiation: A Case Study of a Private University Reaccreditation in North Jakarta - Carmel Meiden; Yosef Dema; Tita Djuitaningsih (Universitas Riau Kepulauan, 2025)
This research examines the structuration of conflicts during the negotiation of audit findings within the context of private university reaccreditation. The study focuses on identifying the key factors that initiate and escalate conflicts, as well as the strategies employed by auditors and university officials to manage and resolve these conflicts. It also explores the influence of power dynamics, communication, and economic constraints on the negotiation process. The research utilizes qualitative methods, including observations of auditor-auditee interactions and document analysis, to investigate the complexities of audit negotiations. The study is anchored in Giddens' Structuration Theory, which provides a framework for understanding how institutional structures and individual actions shape the conflict dynamics. The findings reveal significant power imbalances between auditors and auditees, communication challenges, and economic constraints that contribute to the structuration of conflicts. The study also highlights how procedural rigidity and the struggle to align local practices with international standards exacerbate these conflicts, ultimately impacting the outcomes of the reaccreditation process. The research underscores the need for improved decision-making processes, genuine compliance practices, better resource management, and effective communication to enhance the reaccreditation process. These findings offer valuable insights for policy development and institutional governance in the higher education sector.